2006
DOI: 10.1080/08860220600781245
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Dialysis in Acute Renal Failure

Abstract: The definition of adequate dialysis in acute renal failure (ARF) is complex and involves the time of referral to dialysis, dose, and dialytic method. Nephrologist experience with a specific procedure and the availability of different dialysis modalities play an important role in these choices. There is no consensus in literature on the best method or ideal dialysis dose in ARF. Peritoneal dialysis (PD) is used less and less in ARF patients, and is being replaced by continuous venovenous therapies. However, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
105
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(117 citation statements)
references
References 35 publications
8
105
2
2
Order By: Relevance
“…Four studies (19,20,31,32) did not report parameters that indicate the risk profile of the cohort, such as the proportion of septic and ICU patients. Only seven studies reported an illness severity score (10,15,18,25,27,29,37).…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
See 4 more Smart Citations
“…Four studies (19,20,31,32) did not report parameters that indicate the risk profile of the cohort, such as the proportion of septic and ICU patients. Only seven studies reported an illness severity score (10,15,18,25,27,29,37).…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
“…The mean age of patients ranged from 29.1 to 75.6 years. The causes of AKI were variable, with the most common causes being reported as sepsis (10,15,17,18,22,25,(27)(28)(29)(30)(33)(34)(35)(36)(37), prerenal causes or hypovolemia (6,17,22,26,28,30,32,(35)(36)(37), cardiac failure (10,18,22,30,35,36), postsurgery (10,18,19,26,31,35), and nephrotoxic agents (22,26,35,36). Mortality was reported at hospital discharge (6,15,23,35), at 30 days (10,17,18,27), or not specified.…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
See 3 more Smart Citations